PRACTICE OF POWER IN ILKHANATE: ANALYSIS OF INTERCULTURAL COMMUNICATION AND SOCIAL EXCHANGE - Apipudin Apipudin (Arabic Literature Department, 2023)
Ilkhanate was a Mongol empire located in Persia. There were cultural changes and different forms of practice in exercising government power. However, despite the significance of understanding the practice of power in the Ilkhanate through the lens of communication theories, there is a research gap in exploring the specific dynamics of intercultural communication and social exchange theory within this context. Therefore, this study aims to fill this research gap by examining the interplay between power and communication in the Ilkhanate, mainly through the principles of intercultural communication and social exchange theory. The methodology employed in this research is a comprehensive literature study. The findings of this article highlight the inseparability of communication and power, emphasizing the role of intercultural communication in facilitating harmonious relations between diverse nations, including considerations of race, religion, and customs. Additionally, the rulers of the Ilkhanate strategically employed communication and adapted their policies to gain support from local communities, such as Persians and Arabs, particularly by catering to the Muslim population. This research contributes to understanding power practices and strategies in the Ilkhanate by elucidating their alignment with intercultural communication and social exchange theories.